Acompanhamento do processo produtivo da Cervejaria Nordestina LTDA - Freitas, Daniel Jônatas de Oliveira (Universidade Federal Rural do Semi-Árido, 2021)
Created in 2019 and operating since then, Cervejaria Nordestina, despite being one of the newest craft breweries in the region, already has a loyal consumer market in the city of Mossoró and region, relying on a regular production process, aiming to meet its needs demand. Focusing on the production of its own craft beer, the main product and the biggest difference in relation to its competitors, the company performs and values a meticulous care at each stage of its production process in order to maintain its high-quality standard. Therefore, it is necessary to identify the particularities in each phase of product manufacturing, as well as to get familiarized with the process, from the malt grinding to the final filling, also passing through the part of sanitization and sanitization in order to maintain the quality of the beer produced. With that, this work aims to describe the main activities worked during the internship, in addition to adding a greater practical knowledge of the responsibilities of a chemical engineer acting in his role. The internship period was very important in the practical application of the theory learned during the graduation period. The company offered full conditions for learning and performing the necessary activities during the period.
Keywords: Cerveja artesanal; Processo produtivo; Cervejaria Nordestina; Craft beer; Productive process; ENGENHARIAS::ENGENHARIA MECANICA